F-Wave in the Upper Extremities of Patients with Primary Torsion Dystonia - Semerdjieva, N.; Atanasova, D.; Hranov, G.; Milanov, I. (Нейрофизиология, 2015)
We investigated characteristics of the F-waves in the upper limbs of patients suffering from primary torsion dystonia (PTD) by means of surface-electrode electromyography. Single electric stimulation was used to obtain optimum M-responses from the m. abductor pollicis brevis (median nerve) and m. abductor digiti minimi (ulnar nerve). Ten consecutive supramaximum electrical stimuli were applied to each nerve to obtain F-waves from the wrist. In general, the registered M-response latencies and amplitudes, as well as conduction velocities via all inspected nerves, demonstrated no significant deviations from the normal ranges. Nearly all investigated patients, except one, had normal F-wave minimal latencies. The mean amplitudes of F-waves from both median and ulnar nerves were higher than the average F-wave amplitudes described in the literature. The frequency of occurrence of F-waves in both median and ulnar nerves was greater than in the norm. According to our results, it can be concluded that the amplitude and, to some extent, frequency rather than the latency of F-waves are important in the studies of patients with PTD. Increased amplitudes and frequencies reveal changes in the excitability of alpha motoneurons, which could be accepted as a measure of a disturbed interneuronal balance probably caused by alterations in the suprasegmental control mechanisms related to PTD.